2014
DOI: 10.7448/ias.17.4.19797
|View full text |Cite
|
Sign up to set email alerts
|

Durability of first antiretroviral treatment in HIV chronically infected patients: why change and what are the outcomes?

Abstract: IntroductionFirst antiretroviral therapy (ART) is often switched to simpler, more potent or better tolerated regimens [1, 2]. Although discontinuation rates are frequently studied, the durability of regimens is rarely approached.Materials and MethodsRetrospective study with the following objectives: analyze first ART schemes and their durability in naive patients with chronic HIV-1 and 2 infections, evaluate factors influencing ART change, second-line ART and consequent virologic and immunologic responses. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
0
9
0
1
Order By: Relevance
“…Some studies suggested first antiretroviral therapy was often switched to simpler, more potent, better-tolerated regimens than the replaced regimen [ 37 , 38 ]. Previous studies demonstrated that side effect of patients who changed regimens during the treatment such as toxicity [ 39 ], experienced virological failure and resistance-conferring mutations within the viral genome than the patients who never changed the regimen, mainly reason due to poor compliance [ 40 , 41 ]. Other studies showed that the effect was significant better after changing the regimen, the median CD4+ count increased from 157 cells/μL at baseline to 307 cells/μL in 120 weeks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested first antiretroviral therapy was often switched to simpler, more potent, better-tolerated regimens than the replaced regimen [ 37 , 38 ]. Previous studies demonstrated that side effect of patients who changed regimens during the treatment such as toxicity [ 39 ], experienced virological failure and resistance-conferring mutations within the viral genome than the patients who never changed the regimen, mainly reason due to poor compliance [ 40 , 41 ]. Other studies showed that the effect was significant better after changing the regimen, the median CD4+ count increased from 157 cells/μL at baseline to 307 cells/μL in 120 weeks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of adherence to the medication are necessary for successful medication (7). However, considering the availability of ART, people living with HIV (PLWH) are not uniformly responsive to treatment (8) and there is nearly 50% to 80% of nonadherence to the medication (9)(10)(11) and poor adherence is a primary factor in suboptimal treatment response (12). The reasons for nonadherence are various (13); side effects of the antiretroviral medication such as nausea or anemia and a number of psychological factors play an important role in the impaired adherence to the antiretroviral therapy (14).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of highly active antiretroviral therapy (ART) dramatically reduced AIDS-related mortality such that approximately 30 million people currently live with HIV around the globe ( Hallett et al, 2014 ). However, despite the availability of ART, people living with HIV (PLWH) are not uniformly responsive to treatment ( Moniz et al, 2014 ), and poor adherence is a primary factor in suboptimal treatment response ( Li et al, 2014 ). Incidents of stressful life events predict nonadherence and increased odds of virologic failure ( Safren et al, 2003 ; Mugavero et al, 2009 ), possibly through avoidant coping ( Martinez et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%